Low linolenic soybeans for biodiesel: Characteristics, performance and advantages - Santos, Eleonice Moreira; Piovesan, Newton Deniz; Barros, Everaldo Gonçalves de; Moreira, Maurilio Alves (Fuel, 2012)
Soybean is one of the main raw materials used for biodiesel production. However, the polyunsaturated fatty acids present in soybean seeds are not desirable for this purpose due to their low oxidative stability. Therefore, it is expected that the use of soybean cultivars with low linolenic acid content for biodiesel production will improve its oxidative stability and the cold filter plugging point (CFPP). This work presents the main characteristics, the advantages and performance of low linolenic acid soybean (LL) as compared to a conventional soybean variety (CO) for biodiesel production. The results showed that LL oil and protein contents were similar to those of CO. Phosphatide concentration was higher in LL oil, while total tocopherol content was lower in relation to CO. With respect to LL biodiesel performance, oxidative stability was much higher than that produced from CO, and the CFPP did not change even with the improved fatty acid profile of LL.
Keywords: Soybean; Oxidative stability; Cold filter plugging point; Biodiesel; Fatty acid profile